ANALISIS FAKTOR YANG BERPENGARUH TERHADAP KEJADIAN MALARIA DI WILAYAH PESISIR BERDASARKAN TEORI HL.BLUM - Susilawati Susilawati; Salsabila Prayatna (CV. ADIBA AISHA AMIRA, 2023)
Malaria is a type of infectious disease which is a public health problem today. Malaria is rarely transmitted due to physical contact from one person to another, but malaria is an infectious disease that can be transmitted through mosquito bites or can be infected through blood transfusions. According to WHO, Indonesia is a country that has a high prevalence of malaria. The annual morbidity rate of malaria is based on the results laboratory examination, namely per 1000 population. The purpose of this study was to analyze factors related to malaria prevention behavior in coastal areas. This type of research is a systematic review which is carried out by collecting, selecting and reviewing scientific articles that have topics that are relevant to the research objectives. The variables in this study are the level of knowledge, attitude, level of education, and type of work. This research is a secondary research with the type of research literature review. There are 10 research articles that are in accordance with thetopic of malaria, research related to the variables studied which were obtained from the results of submissions through Google Scholar, PubMed, and Science Direct. Based on the results of a review of research articles, it was found that as many as 1 (10%) stated that there was no relationship between knowledge and malaria prevention behavior, as many as 2 (25%) research articles which stated that there was no relationship between type of work and malaria prevention behavior, as many as 2 (25%) 20.2%) of articles stated that there was no relationship between education level and malaria prevention behavior, as many as 1 (10%) articles stated that there was no relationship between respondents' attitudes and malaria prevention behavior. While as many as 5 (50.5%) articles stated that there was a relationship between knowledge and malaria prevention behavior, and as many as 4 (60.5%) research articles which stated that there was a significant relationship between type of work and malaria prevention behavior, as many as 3 (55.5%) %) of research articles which stated that the majority of people with highereducation levels performed malaria prevention behavior well, as many as 5 (60.5%) articles which stated that there was a relationship between respondents' attitudes and malaria prevention behavior in the community